Sleep, Musculoskeletal Injuries, and Hormonal Status in Different Training Stages in Adolescent Athletes - Luísa de Sousa Nogueira Freitas; Samuel Penna Wanner; Samuel Silva; Eduardo Stieler; Fernanda Viegas Paulo; Marina Costa Pinto; Lucas Alves Facundo; Marco Tulio de Mello; Andressa Silva (Sleep Science)
Objective This study aimed to compare sleep, musculoskeletal injuries, and testosterone and cortisol levels in different training stages in adolescent athletes, and to investigate the association between these variables.